Ethnicity, space and human development in poor urban communities: Commune 6 in cartagena de indias, Colombia (2020)
Cartagena de Indias has the highest social exclusion among the main cities in Colombia. This paper evaluates human development and the determinants of poverty in the commune 6, where the Afro-Colombian population predominates. Based on the structure of the analytical framework of urban poverty, capabilities and opportunities, and an ad hoc database with probit model as an empirical strategy, we elaborate a differentiated poverty profile for this large area, applying spatial criteria. The results reveal that the labour ethnic variables -with conclusive evi- dence in favour of white people- and social capital explain the deprivations in this community.